Integrating Digital Marketing and Maritime Branding for Cadet Recruitment in STIP Indonesia - Ratnasari, Ni Nyoman Sri; Fachruddin, Imam; Harahap, Ramadhan Hasri; Mudakir (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2025)
This qualitative study investigates the integration of digital marketing and maritime branding strategies at the Sekolah Tinggi Ilmu Pelayaran (STIP) Indonesia to enhance cadet recruitment. Through in-depth interviews, focus group discussions, and document analysis with key internal and external stakeholders, the research identifies a significant gap between the institution's official